Techniko-takticeskie dejstvija vratarej v pljažnom futbole pri organizacii nacala ataki - Muchamedzyanov, R. R.; Petrikevich, A. S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The competition period is one of the main indicators of the effectiveness of the training process. It is in the process of games that the positive / negative aspects of the preparedness of the athletes are fully manifested. Thanks to the registration of technical and tactical indicators in the process of competitive activity, extensive material has been accumulated about the technical and tactical actions of goalkeepers of high qualification in beach football. On the basis of further study of the indicators it is possible to give practical advice to the coaches of the beach soccer teams regarding the training of goalkeepers. These recommendations can bring the team to high sports results.